‘Gambilng’ Cropping Patterns: Understanding Karo’s Vegetable Farmers Point of View to Cope with Risks and Uncertainties - Sri Alem Br. Sembiring (PERSPEKTIF, 2023)
This paper aims to discuss the coping mechanisms of a community in dealing with risks and uncertainties in new situations that have never been part of their local knowledge. The problem is focused on how the subject (farmer) formulates risk and uncertainty, and shows their coping mechanisms to deal with the complexity of the problem. The cultural approach is an important reference for understanding the empirical phenomenon being studied, combined with the concept of dynamic local knowledge and the concept of risk. Data were collected through fieldwork using an emic view approach with observation-participation techniques as well as in-depth interviews and qualitative data analysis processes. This study concludes that farmers have a risk conception which they call “try it out” on 4 sources of risk (air, pest, price, volcanic ash of Mount Sinabung) and develop coping mechanisms through variations in cropping patterns, even the type of 'gambling' as an opportunity for the complexity of the risks that occur. The risk symbols are also classified into 2 types of distribution; individual and communal. The ability to cope with each type proves the innovative capacity of the subjects, which is related to the dynamics of knowledge and the learning process in their community.